Effect of different protein and energy levels in concentrate diets on nutrient intake and milk yield of Saanen x Etawah Grade goats - . Supriyati; R. Krisnan; I.G.M. Budiarsana; L. Praharani (Jurnal Ilmu Ternak dan Veteriner, 2016)
Dairy goat contributes to food and nutrition security. However, information on nutrient consumption and milk yield, as well as milk composition of Saanen x Etawah (SAPERA) grade goat is limited. This experiment was done to evaluated nutrient intake, milk yield and its composition of lactating SAPERA goats fed with different levels of dietary energy and protein in concentrate diet. Thirty multiparous SAPERA goats were used in a randomized block design with three treatments (R1, R2 and R3) and ten replications for 12 weeks of lactation. The concentrate diets were formulated to contain: 18% CP and 72% TDN (R1), 17% CP and 75% TDN (R2), 16% CP and 78% TDN (R3). Those does were penned individually, and fed by basal diet (fresh chopped King Grass ad libitum, 500 g of fresh mixed forages) and 1 kg of experimental concentrate. Results showed that the treatments had significant (P<0.05) effects on CP, DIP, Ca, P intakes and FCR but had no significant (P>0.05) effects on DM and TDN intake. No significant differences were found in milk yield and milk composition between treatments. In conclusion, this trial suggested that the best feed for lactating SAPERA goats was the mixture of chopped grasses, mixed forages and concentrate diets (16% CP and 78% TDN) with 160 g/kg CP and 750 g/kg TDN of the total DM, produced a milk of 1.55 kg/d with 90 g/day of milk fat, 43 g/day of milk protein and 75 g/day of milk lactose.